Assisted Reproductive Technology: Techniques and Limitations - Begum, Mosammat Rashida (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Infertility is a source of social and psychological suffering for both men and women and can place great pressure on the relationship within the couple. One in six couples of any society remains infertile and 10% of them need help of assisted reproductive technology (ART). ART refers to all technology where gametes are manipulated outside the body. In-vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) are the commonest of all type of ART. Bilateral tubal block, endometriosis, severe oligospermia, and azoospermia are the commonest indications for ART. Whoever is responsible for infertility women are usually treated for superovulation, which sometimes involves risk of the patient. Collection of oocyte is also invasive. Result of treatment in terms of pregnancy is not very satisfactory. Average pregnancy rate is 30%- 34% worldwide. Abortion and congenital anomaly rate is a bit higher than normal population, which is related to age of the female partner not related to the procedure. There are a number of barriers in this treatment like high cost of treatment, poor result, social stigma and superstitious believe. In addition to creating family by means of assisted reproductive technology, it has made a new dimension for distressed infertile couple. DOI: 10.3329/jbcps.v26i3.4197 J Bangladesh Coll Phys Surg 2008; 26: 135-141